Aplikasi Monitoring dan Screening Covid-19 Menggunakan Metode Certainty Factor dan Forward Chaining - Nur Aprilia; Fauziah Fauziah; Ratih Titi Komala Sari (Universitas Indraprasta PGRI Jakarta, 2021)
Coronavirus disease 2019 or COVID-19 caused by SARS CoV 2 is a tragedy in the world of global health. Even the World Health Organization (WHO) has stated that the corona virus outbreak is a Public Health Emergency of International Concern (PHEIC) or an international public health emergency. Not only has an impact on health but this virus outbreak also has a major impact in various sectors such as disruption of the country's economy, obstruction of the teaching and learning process and so on. This impact is caused by the rapid spread of the virus. Therefore, the authors designed a monitoring and screening application for COVID-19 using certainty factor and forward chaining methods which aim to make it easier for people to monitor the spread of the COVID-19 virus in real time and be able to carry out early screening for COVID-19. Both of these methods produce a system diagnosis with the same results, that is, someone is indicated as SUSPECT COVID-19.